A Cognitive Approach to Mathematical Mapping: From Classical Education to Meaningful Environmental Learning - Araújo, Rayka M. A.; Peixoto, Josana de Castro; Fontes, Liviam Santana; Napolitano, Hamilton Barbosa (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
This study examines how integrating a cognitivist approach with the principles of classical education can promote meaningful learning and critical thinking in addressing contemporary environmental and sustainability challenges, particularly through the synergy of MathMap strategies. This research draws upon the liberal arts in dialogue with David Ausubel’s theory of meaningful learning. This synthesis is explored for its potential to enrich pedagogical practices, anchor new knowledge in pre-existing cognitive structures, and enhance the understanding of environmental issues. Grounded in cognitivist and classical frameworks, as well as the principles of critical environmental education, the study aligns with education for sustainable development from the United Nations, which emphasizes education for sustainability through critical and reflective engagement. The findings suggest that this approach contributes significantly to the development of reflective, ethical, and critical individuals capable of navigating complex sustainability issues.